Reviewing the reviews: the Global Compacts' added value in access to asylum procedures and immigration detention - Atak, Idil; Grundler, Maja; Endres de Oliveira, Pauline; Bast, Jurgen; Guild, Elspeth; Maple, Nicholas; Vanyoro, Kudakwashe; Wessels, Janna; Zyfi, Jona (Frontiers in Human Dynamics, 2023)
The Global Compact for Migration and the Global Compact on Refugees are based on binding international law instruments whose provisions they complement with “best practice” standards related to the treatment of refugees and other migrants. Although the Compacts are non-binding, they provide for review mechanisms to promote compliance with Compact standards. Such oversight is important to achieve progress in implementing the Compacts' commitments. Yet, the current top-down and State-led review process does not offer an efficient platform for identifying cases of non-adherence to Compact standards. This article uses a case study approach to highlight instances of non-compliance with Compact standards in Canada, South Africa, and the European Union. We use a functionalist method of comparison to analyze State practice in these three regions in relation to (i) use of immigration detention and (ii) access to the asylum procedure, with access to healthcare as a cross-cutting issue. The article discusses how the Compacts' review mechanisms could be improved and their added value in terms of their impact on domestic migration policies. It argues that both Compact review and implementation can be improved through increased civil society participation.